The relevance of non-legal technical and scientific concepts in the interpretation and application of the law of the sea : an analysis of the United Nations convention on the law of the sea - Guy, Neil Raymond (Institute of Marine and Environmental Law, 2014)
Bibliography: p. 363-375.